A Stylistic Study of Cohesion in Relation to Narrative Techniques in Religious Discourse (Journal of the College of Education for Women, 2020)
Cohesion is well known as the study of the relationships, whether grammatical and/or lexical, between the different elements of a particular text by the use of what are commonly called 'cohesive devices'. These devices bring connectivity and bind a text together. Besides, the nature and the amount of such cohesive devices usually affect the understanding of that text in the sense of making it easier to comprehend. The present study is intendedto examine the use of grammatical cohesive devicesin relation to narrative techniques. The story of Joseph from the Holy Quran has been selected to be examined by using Halliday and Hasan's Model of Cohesion (1976, 1989). The aim of the study is to comparatively examine to what extent the types of grammatical cohesive devices and their frequencies and densities are affected by thetechniques of narration, namely, internal and external or as commonly known as conversational and narrative. The researcher has come into the conclusion that the grammatical cohesive devices form one third of the story and accordingly, they affect the structure and interpretation of the text. Moreover, thegrammatical cohesive devices are more frequent in the conversational part when compared to the narrative part. It is also concluded that the endophoric reference is the dominant category in the conversational and narrative parts of the story, unlike the exophoric that can be identified only in relation to the background knowledge of the outside situation.